2023
DOI: 10.1088/1402-4896/ad14d6
|View full text |Cite
|
Sign up to set email alerts
|

QTN-VQC: an end-to-end learning framework for quantum neural networks

Jun Qi,
Chao-Han Yang,
Pin-Yu Chen

Abstract: This work focuses on investigating an end-to-end learning approach for quantum neural networks (QNN) on noisy intermediate-scale quantum devices. The proposed model combines a quantum tensor network (QTN) with a variational quantum circuit (VQC), resulting in a QTN-VQC architecture. This architecture integrates a QTN with a horizontal or vertical structure related to the implementation of quantum circuits for a tensor-train network. The study provides theoretical insights into the quantum advantages of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…These algorithms leverage quantum entanglement to address fundamental machine learning challenges, such as function approximation and classification [34,35]. More studies about variational quantum algorithms and circuits can be found here [36]. This innovation has facilitated the development of hybrid quantum-classical algorithms, adaptable for use on existing Noisy Intermediate-Scale Quantum (NISQ) devices.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms leverage quantum entanglement to address fundamental machine learning challenges, such as function approximation and classification [34,35]. More studies about variational quantum algorithms and circuits can be found here [36]. This innovation has facilitated the development of hybrid quantum-classical algorithms, adaptable for use on existing Noisy Intermediate-Scale Quantum (NISQ) devices.…”
Section: Introductionmentioning
confidence: 99%